Bioactive Compounds and Antioxidant Activity in Some Fresh and Canned Aromatic Herbs - Sanda ANDREI; Andrea BUNEA; Constantin BELE; Cristina TUDOR; Adela PINTEA (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology, 2018)
The chlorophylls, carotenoids, total polyphenols contents and antioxidant activity in fresh and stored Parsley, celery and dill leaves were comparatively determined by spectrophotometric and high performance liquid chromatography (HPLC) methods. Results indicated that freezing does not induce significant changes in chlorophyll concentration. Drying induces significant decreases, varying according to the analyzed plant; parsley (60%), followed by dill (56.4%) and celery (45.3%). The carotenoids identified in all plants were lutein, b-carotene and cis-β-carotene. Fresh parsley leaves showed the highest total carotenoid concentration (21.64 mg/100g FW), followed by celery (15.41 mg/100g FW) and dill (14.95 mg/100g FW). Total polyphenols had an average concentration of 2.15 mg/g FW in parsley; 2.7 mg/g FW in dill and almost the double, 4.13 mg/g FW in celery. Drying of leaves induced a decrease with approximately 50% of the total polyphenol concentration, while freezing, did not significantly affect it. The highest antioxidant activity was observed in the dill, followed by parsley and celery. In both types of methods (freezing and drying in the oven), decreases in antioxidant activity were observed.